Faktor-Faktor yang Mempengaruhi Kepatuhan Berobat Pasien Kanker Payudara yang Menjalani Kemoterapi di RSUP Dr. Mohammad Hoesin Palembang - Indah, Furqan; Qodir, Nur; Legiran, Legiran (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Breast cancer affects 2.1 million women every year and is the biggest cause of cancer death in women in the world. Therapy for breast cancer is one of them with chemotherapy. Adherence is required in undergoing treatment to avoid the progression and recurrence of the disease. This type of research is observational descriptive with consecutive sampling techniques. The sample of this study were breast cancer patients who underwent chemotherapy at RSUP Dr. Mohammad Hoesin in September 2019 who met the inclusion and exclusion criteria. The instruments in this study were the Patient Compliance Questionnaire Undergoing Chemotherapy and the Center for Epidemiologic Studies Depression Scale (CES-D) questionnaire. In this study, 49 breast cancer patients were the subjects of the study. The results of the study the most age group were 50-54 years with a percentage of 22.4% (n=11), the level of education was the secondary school 42.9% (n=21), and family income below the provincial minimum wage 57,1% (n=28). All subjects (n=49) had insurance and chemotherapy side effects. According to the assessment, there were 24.5% (n=12) were depressed, 91.8% (n=45) obedient and not compliant with treatment by 8.2% (n=4). The reason for compliant treatment is the desire to recover and family. Patients not complying is because of the distance of the house and the side effects. Five factors that influence the compliance of treatment are social and economic, health care team and system, condition, therapy, and patient-related factors.